Ultra-estrutura dos mastócitos de diferentes tipos histológicos de mastocitoma em cães - Sueiro, F.A.R. [UNESP]; Daleck, C.R. [UNESP]; Alessi, A.C. [UNESP] (Universidade Federal de Minas Gerais (UFMG), Escola de Veterinária, 2002)
Este trabalho teve por objetivo estudar as diferenças ultraestruturais de mastócitos neoplásicos de diferentes tipos histológicos de mastocitoma em cães, usando microscopia eletrônica de transmissão Os resultados mostraram que o núcleo e os grânulos citoplasmáticos são as estruturas mais indicadas para se avaliar o grau de anaplasia celular e o estádio de indiferenciação do tumor.

The objective of this work was study the ultrastructural differences among the different histologic types of mast cell tumors in dogs collected in vivo. The ultrastructural analyses showed that the nuclei and cytoplasmic granules characteristics are the best structures to be appointed on evaluating the undifferentiation stage of this tumor.
Mast cell ultrastructure in different types of canine mast cell tumor
Keywords: Dog; mast cell tumor; Ultrastructure; Cão; Mastocitoma; Ultraestrutura